Cellular and physiological circadian mechanisms drive diurnal cell proliferation and expansion of white adipose tissue - Aleix Ribas-Latre (Nature Portfolio, 2021)
During the expansion of adipose tissue adipocyte progenitor cells proliferate and undergo adipogenesis. Here, the authors show that adipocyte progenitor cell proliferation in visceral adipose tissue has a diurnal pattern, which is dependent on both energy intake and the circadian clock.